Th17 cells are involved in the local control of tumor progression in primary intraocular lymphoma. - Claire Galand (Public Library of Science (PLoS), 2011)
Background Th17 cells play an important role in the pathogenesis of many autoimmune diseases, but despite some reports of their antitumor properties, too little is known about their presence and role in cancers. Specifically, knowledge is sparse about the relation of Th17 to lymphoma microenvironments and, more particularly, to the microenvironment of primary intraocular B-cell lymphoma (PIOL), an aggressive lymphoma with a poor prognosis. Methods and principal findings In this work, we investigated the presence of Th17 cells and their related cytokines in a syngeneic model of PIOL, a subtype of non-Hodgkin lymphoma. The very small number of lymphocytes trafficking in normal eyes, which represent a low background as compared to tumor-bearing eyes, allows us to develop the present model to characterize the different lymphocyte subsets present when a tumor is developing. IL-21 mRNA was expressed concomitantly with IL-17 mRNA in tumor-bearing eyes and intracellular expression of IL-17A and IL-21 in infiltrating CD4(+) T lymphocytes. Interestingly, IL-17A production by T cells was negatively correlated with tumor burden. We also showed that IL-21 but not IL-17 inhibits tumor cell proliferation in vitro. Conclusions These data demonstrate that IL-17A and IL-21-producing CD4(+) T cells, referred as Th17 cells, infiltrate this tumor locally and suggest that Th17-related cytokines may counteract tumor progression via IL-21 production. Thus, Th17 cells or their related cytokines could be considered to be a new therapeutic approach for non-Hodgkin B-cell lymphomas, particularly those with an ocular localization.